Determinants of Ikat Weaving Consumption in a Local Creative Economy - Y. Koli, Damaris; Rohanie Mbado, Margarethy; Alex Serang, Roberth; Nustanti Ndaomanu, Dian; J. S. Dethan, Jemmy (Universitas Tanjungpura, 2026)
Ikat weaving is a cultural product with significant symbolic and economic value in the development of a local culture-based creative economy, particularly in East Nusa Tenggara Province, Indonesia. This study aims to examine how social identity, cultural identity, textile diversity, consumer preference, and ikat weaving preference shape ikat weaving consumption patterns. A quantitative research design was employed using a survey of 97 respondents who had experience purchasing or using ikat weaving from East Nusa Tenggara. Data were analyzed using a structural equation modeling approach. The results show that social identity has a significant influence on cultural identity and consumer preference. Cultural identity affects perceptions of textile diversity, which subsequently shape preferences for ikat weaving. Consumer preference is found to have the strongest influence on ikat weaving consumption patterns. Mediation analysis indicates that most relationships operate through direct pathways based on identity and preference rather than complex indirect mechanisms. These findings suggest that ikat weaving consumption is not merely an economic decision but represents a socio-cultural process reflecting collective identity. This study provides empirical insights into cultural product consumption and supports the development of sustainable local creative economy strategies.